Increasing the accessibility of long-acting reversible contraceptives through nurse-led insertions: A cost-benefit analysis. Issue 1 (February 2020) - Botfield, Jessica R.; Lacey, Sarina; Fleming, Kirsteen; McGeechan, Kevin; Bateson, Deborah
Abstract: Background: Long-acting reversible contraceptives (LARCs) are highly effective in preventing pregnancy; however, uptake remains relatively low in Australia. Extending provision by registered nurses (RNs) with the required knowledge and skills may increase accessibility of these contraceptive methods. Methods: A cost-benefit analysis was undertaken to assess the impact of Australian women switching from an oral contraceptive pill (OCP) to a LARC, or initiating the use of a LARC for women not currently using any form of contraception, over five years. The additional impact of 20% of the increase in LARC insertions being carried out by RNs was also modelled. Findings: If women using the OCP switched to LARC, in-line with LARC uptake in comparable countries, net savings are estimated at 68 million over five years, given the significant out-of-pocket expenses associated with the OCP. For women using no contraception who adopt a LARC, in-line with uptake in comparable countries, the value of avoided abortions and miscarriages is 20 million over five years. If 20% of women who switch to a LARC are provided with services by a RN (compared to a GP), there would be an additional cost saving to government of 2.7 million. Further savings for women due to lower out-of-pocket costs for insertion are valued at 500, 000 over five years. Conclusion: Enabling RN-led LARC insertion is a cost-effective way of increasing accessibility to these contraceptive methods. The creation of Medicare Benefits Schedule item numbers for RNs appropriately trained in LARC insertion and removal would have benefits for both women and the Australian government.